2012
DOI: 10.5194/amt-5-1869-2012
|View full text |Cite
|
Sign up to set email alerts
|

Soot reference materials for instrument calibration and intercomparisons: a workshop summary with recommendations

Abstract: Abstract. Soot, which is produced from biomass burning and the incomplete combustion of fossil and biomass fuels, has been linked to regional and global climate change and to negative health problems. Scientists measure the properties of soot using a variety of methods in order to quantify source emissions and understand its atmospheric chemistry, reactivity under emission conditions, interaction with solar radiation, influence on clouds, and health impacts. A major obstacle currently limiting progress is the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
183
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(196 citation statements)
references
References 78 publications
9
183
0
4
Order By: Relevance
“…The registration filter is not itself a calibration standard whose absorptance is independently known a priori. A 2011 workshop described by Baumgardner et al (2012) identified a general lack of such standards, concluding that "there are no procedures to calibrate filter-based instruments that use the measurement of light attenuation to derive the absorption coefficient." Optical components are available with certified values of reflectance or transmittance, but these standards do not mimic the observed scattering phase functions of filter media and filter samples.…”
Section: Methods and Calibrationmentioning
confidence: 99%
“…The registration filter is not itself a calibration standard whose absorptance is independently known a priori. A 2011 workshop described by Baumgardner et al (2012) identified a general lack of such standards, concluding that "there are no procedures to calibrate filter-based instruments that use the measurement of light attenuation to derive the absorption coefficient." Optical components are available with certified values of reflectance or transmittance, but these standards do not mimic the observed scattering phase functions of filter media and filter samples.…”
Section: Methods and Calibrationmentioning
confidence: 99%
“…Refractory black carbon (BC) concentrations were also measured using a DMT single-particle soot photometer (SP2; Stephens et al, 2003;Schwarz et al, 2010), with optics and electronics upgraded to be functionally identical to the current SP2 model D. The SP2 was calibrated with Aquadag as recommended by Baumgardner et al (2012) and Laborde et al (2012). Further details on the aerosol instrumentation and measurements will be provided in a future manuscript.…”
Section: Aerosol Instrumentationmentioning
confidence: 99%
“…The incandescence signal was calibrated (three times, at the beginning, half way through and at the end of the measurement campaign) using mobility size selected fullerene soot particles (Alpha Aesar; #FS12S011) which is recommended for SP2 calibration as it gives similar SP2 responses as ambient rBC Baumgardner et al, 2012;Laborde et al, 2012a). The fullerene soot particles were selected by mobility diameter using a differential mobility analyser (DMA) and the corresponding particle masses were calculated using the effective density data provided in .…”
Section: Calibrationmentioning
confidence: 99%
“…The scattering signal was calibrated twice (at the beginning and half way through the measurement campaign) using spherical polystyrene latex size standards with a diameter of 269 nm (Thermo Scientific, formerly Duke Scientific). More details on SP2 calibration and calibration standard material can be found in Baumgardner et al (2012), Laborde et al (2012b) and .…”
Section: Calibrationmentioning
confidence: 99%